2006
DOI: 10.1007/s00426-005-0003-9
|View full text |Cite
|
Sign up to set email alerts
|

The locus and modulation of the location negative priming effect

Abstract: Responding to the location of a target is slower when it appears at a recent distractor location [ignored-repetition (IR) trial] than when it arises at a new position [control (CO) trial], defining the location negative priming (NP) effect. On IR trials, both the distractor location and response are from the prior trial, and the locus question asks whether the delayed responding that arises is caused by the reused distractor position (i.e., a location locus) or the need to execute a distractor output (i.e., a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
1
12
1
Order By: Relevance
“…Comparing response control with control trials revealed that the need to execute a prior distractor response did not affect response latency. This result contradicts the prediction derived from the response inhibition account that has been put forward to explain visual spatial negative priming Guy & Buckolz, 2007;Guy et al, 2006).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Comparing response control with control trials revealed that the need to execute a prior distractor response did not affect response latency. This result contradicts the prediction derived from the response inhibition account that has been put forward to explain visual spatial negative priming Guy & Buckolz, 2007;Guy et al, 2006).…”
Section: Discussioncontrasting
confidence: 55%
“…To test the response inhibition account of spatial negative priming, Buckolz et al (2004;for replications, see Fitzgeorge, Buckolz, & Khan, 2011;Guy & Buckolz, 2007;Guy, Buckolz, & Khan, 2006) isolated the influence of reexecuting a previously irrelevant response in a spatial negative priming task by modifying the location-response assignment. Participants had to locate a dark blue rectangle by manually pressing a locationassigned response key while ignoring a light blue distractor rectangle.…”
Section: Introductionmentioning
confidence: 99%
“…Neill, 2007). In particular, in spatial NP tasks, NP can be found even when targets and distractors are presented with a spatial separation of up to 12°of visual angle (Chao & Yeh, 2005; see also Guy & Buckolz, 2007, for evidence showing that targetdistractor distance seems to play no role in spatial NP), whereas in identity NP tasks, NP usually starts to diminish when the target and distractor are separated by no more than 3°of visual angle (e.g., Fox, 1994;Ruthruff & Miller, 1995). In addition, in identity NP tasks, the selection of a target object in the prime displays often seems to be a precondition for NP to occur (though, see Joordens et al, 2006, for an exception; see also the work by Milliken and colleagues, 1998) whereas, in spatial NP tasks, no selection of a target location is needed for NP to occur (Guy, Buckolz, & Pratt, 2004;Park & Kanwisher, 1994).…”
Section: Np In Different Modalitiesmentioning
confidence: 99%
“…This finding can be exclusively explained by assuming distractor location inhibition or the retrieval of inconsistent prime episode information attached to the previous distractor location. What is more, feature mismatching is frequently regarded to be an irrelevant or, at most, a very subordinate factor in visuospatial negative priming, which is indicated by the fact that many recent visuospatial priming studies have not even excluded or controlled feature mismatching as an explanation of their spatial priming effects (Buckolz, Avramidis, & Fitzgeorge, 2008;Buckolz et al, 2004;Gibbons, 2006;Guy & Buckolz, 2007;Guy, Buckolz, & Khan, 2006;Guy, Buckolz, & Pratt, 2004). It has been assumed that a process that detects mismatching features between the current probe target and the previous prime distractor object comes into play only under very specific circumstances that have not been investigated thoroughly Tipper et al, 1995).…”
mentioning
confidence: 99%